2010
DOI: 10.1103/physrevb.81.085124
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nature of the 500 meV peak inLa2xSrxCuO4observed with resonant inelastic x-ray scattering at t

Abstract: We present a comprehensive study of the temperature and doping dependence of the 500 meV peak observed at q = ͑ ,0͒ in resonant inelastic x-ray scattering ͑RIXS͒ experiments on La 2 CuO 4 . The intensity of this peak persists above the Néel temperature ͑T N = 320 K͒, but decreases gradually with increasing temperature, reaching zero at around T = 500 K. The peak energy decreases with temperature in close quantitative accord with the behavior of the two-magnon B 1g Raman peak in La 2 CuO 4 and, with suitable re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 93 publications
(164 reference statements)
4
50
0
Order By: Relevance
“…15 shows that these paramagnons are compatible with very high T c superconductivity supported by spin fluctuations. As far as higher order spin excitations are concerned a mixture of single magnon and bimagnon has been observed with Cu L 3 RIXS, 16 while it has been demonstrated that RIXS at the Cu K edge gives experimental access to bimagnon 7,17 in agreement with the theoretical work of Refs. 18-21.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…15 shows that these paramagnons are compatible with very high T c superconductivity supported by spin fluctuations. As far as higher order spin excitations are concerned a mixture of single magnon and bimagnon has been observed with Cu L 3 RIXS, 16 while it has been demonstrated that RIXS at the Cu K edge gives experimental access to bimagnon 7,17 in agreement with the theoretical work of Refs. 18-21.…”
Section: Introductionsupporting
confidence: 81%
“…It has been already demonstrated by Ellis et al 17 that the accurate fitting of the bimagnon energy requires the inclusion of the magnon-magnon interaction so that there is no point in doing this exercise in the present case. Instead it is interesting to test at Cu K edge the basic approach we used in the O K case, with the obvious needed changes.…”
Section: B Comparison Between Cu K and Cu L3 Rixsmentioning
confidence: 92%
See 1 more Smart Citation
“…The growths followed the protocols already reported for the nonsuperconducting samples [24][25][26] .…”
Section: Methodsmentioning
confidence: 99%
“…The quasi-elastic background, which is expected to depend on temperature, was subtracted by using a fit to the energy-gain (hω <0) side of the spectrum as the background. 42 That the spectra overlap with the exception of the NIR feature indicates that the background subtraction procedure is correct, and that the only temperature dependent part is the NIR feature. The upturn of the intensity at ∼1.2 eV is consistent with that observed in Ref.…”
Section: Barium-doped X=1/8 Samplementioning
confidence: 99%